Penerapan Practical Life Spooning Pada Pembiasaan Kemandirian Siswa Anak Berkebutuhan Khusus Di SLBIT Smart Insani Lampung Tengah - Dewi Kurniawati (JISEI: Journal of Islamic Studies and Educational Innovation, 2026)
Independence is a crucial aspect of development for children with special needs and needs to be fostered through daily habituation activities. One form of practical life activity that can be used to promote independence is spooning, or using a spoon independently. This study aims to describe the implementation of practical life spooning activities in fostering independence among children with special needs and to identify changes in their ability to perform eating activities independently. This research employed a qualitative method with a descriptive approach. The research subjects were children with special needs in special or inclusive educational settings. Data were collected through observation, interviews, and documentation. The findings indicate that the implementation of practical life spooning activities, carried out gradually, individually, and adjusted to the characteristics and needs of the children, can improve their independence, particularly in eating activities, fine motor coordination, and self-confidence. Therefore, practical life spooning activities are effective as a habituation strategy to foster independence in children with special needs.